The cross-sectional association between chemerin and bone health in peri/pre and postmenopausal women: results from the EPIC-Potsdam study - Menzel, Juliane (Menopause, 2018)
OBJECTIVE: Recent in vitro data suggested that the novel adipokine chemerin may influence bone health. However, only limited evidence of the relationship between chemerin and bone health in humans is available. Therefore, this study aimed to investigate the association between chemerin and broadband ultrasound attenuation (BUA) in peri/premenopausal and postmenopausal women. METHODS: Data from the German population-based European Prospective Investigation into Cancer and Nutrition-Potsdam cohort comprising 404 peri/premenopausal and 279 postmenopausal women were analyzed. Multivariable-adjusted analysis of covariance including age, body mass index, waist circumference, smoking status, education, physical activity, alcohol consumption, and hormone use was used to investigate potential relationships between the adipokine and BUA levels in peri/premenopausal and postmenopausal women, respectively. RESULTS: The concentrations of chemerin were lower in peri/premenopausal women (median 118.0 ng/mL, interquartile range [IQR] 99.2-135.0), compared with postmenopausal women (median 140.0 ng/mL, IQR 121.0-167.0). In peri/premenopausal women chemerin was inversely associated with BUA levels; after multivariable adjustment, a 10% increase in the chemerin concentration was significantly associated with 0.83 dB/MHz lower BUA levels (P = 0.0006). In postmenopausal women chemerin was not related to BUA levels (P = 0.8). CONCLUSION: The present study provides evidence for an inverse association between chemerin and BUA in peri/premenopausal women. Therefore, the study suggests that high chemerin concentrations may minimize peak bone mass and thereby may promote age-related bone loss. Further studies are needed to investigate the role of chemerin in bone homeostasis in peri/premenopausal and postmenopausal women.